Meningkatkan Kemampuan Guru Dalam Pembuatan Soal Hots Menggunakan Aplikasi Canva - Iwan Tri Riyadi Yanto; Azty Acbarrifha Nour; Sumargiyani (ReTII, 2023)
Abstract written in Indonesian and English using Times New Roman 11 pt, single-spaced. An abstract is the essence of all the contents of the paper. The abstract includes the main problems, the purpose of the service, the method of implementing the service, and the results achieved. Abstract no more than 200 words. Under the abstract, include 3-6 keywords that are specific to the manuscript.. With the rapid advancement of information technology, teachers must become more adept at incorporating it into instructional activities. Information technology can be utilized to develop Higher Order Thinking Skill (HOTS) questions in addition to being used as a learning medium. In practice, teachers’ use of information technology to create or develop HOTS questions is still not optimal. Canva is one program that may be used to design HOTS questions. This service is designed to help participants improve their ability to create HOTS questions. All Muhammadiyah Beji Elementary School teachers in Gunung Kidul Regency receive training and mentoring through this program. The training sessions were divided into two sections. The first stage included instruction on how to use the Canva program with Artificial Intelligent. The first part of instruction focuses on utilizing the Canva program and its artificial intelligence-enhanced help features. The second step involves training in the creation of HOTS questions for mathematics subject matter. The teacher focuses on producing HOTS questions using the Canva program, which was taught in the first part of training, in the second stage. Based on the evaluation, it can be concluded that understanding of the Canva application and the facilities in the Canva application, including the AI technology in the application, has increased, and 66.67% of participants expressed satisfaction with the training by giving 10 points on a scale of 1-10.